Conditions Governing Food Protein Amyloid Fibril Formation. Part II: Milk and Legume Proteins. Issue 4 (13th June 2019) - Lambrecht, Marlies A.; Jansens, Koen J.A.; Rombouts, Ine; Brijs, Kristof; Rousseau, Frederic; Schymkowitz, Joost; Delcour, Jan A.
Abstract: Both intrinsic and extrinsic factors impact amyloid formation of food proteins. We here review the impact of various conditions and food constituents on amyloid fibrillation of milk and legume proteins. Much less is known about casein and legume protein amyloid‐like fibril formation than about that of whey proteins such as β‐lactoglobulin, α‐lactalbumin, and bovine serum albumin. Proteins of both sources are often studied after heating under strong acidic (pH < 3) conditions. The latter induces changes in protein conformation and often peptide hydrolysis. At higher pH values, alcohols, chaotropic and/or reducing agents induce the conformational changes required to enhance fibrillation. Different types of food proteins can impact each other's fibrillation. Also, the presence of other food constituents can enhance or reduce it. No general conclusions on the mechanisms or impact of different food constituents on food proteins can be made. Optimal conditions for AF formation, that is, heating for several days at low pH, are rare in food processing. However, this does not exclude the possibility of AF formation in food products. For example, slow cooking of hydrolyzed proteins may enhance it. Future research should focus on the prevalence of AFs in complex food systems or model systems relevant for food processing.